Lectin complement protein Collectin 11 (CL-K1) and susceptibility to urinary schistosomiasis. - Justin S Antony; Olusola Ojurongbe; Peter G Kremsner; Thirumalaisamy P Velavan (Public Library of Science (PLoS), 2015)
BACKGROUND:Urinary Schistosomiasis is a neglected tropical disease endemic in many sub Saharan -African countries. Collectin Kidney 1 (CL-K1, encoded by COLEC11 on chromosome 2p25.3), a member of the vertebrate C-type lectin super family, has recently been identified as pattern-recognition molecule (PRR) of the lectin complement pathway. CL-K1 is preferentially expressed in the kidneys, but also in other organs and it is considered to play a role in host defense to some infectious agents. Schistosome teguments are fucosylated and CL-K1 has, through its collagen-like domain, a high binding affinity to fucose. METHODOLOGY/PRINCIPAL FINDINGS:We utilized a Nigerian study group consisting of 167 Schistosoma haematobium infected individuals and 186 matched healthy subjects, and investigated the contribution of CL-K1 deficiency and of COLEC11 polymorphisms to infection phenotype. Higher CL-K1 serum levels were associated with decreased risk of schistosome infection (P corr = 0.0004). CL-K1 serum levels were differentially distributed between the COLEC11 genotypes and haplotypes observed. The non-synonymous variant p.R216H was associated with the occurrence of schistosomiasis (OR = 0.44, 95%CI = 0.22-0.72, P corr = 0.0004). The reconstructed COLEC11*TCCA haplotypes were associated with higher CL-K1 serum levels (P = 0.002) and with decreased schistosomiasis (OR = 0.38, 95%CI = 0.23-0.63, P corr = 0.0001). CONCLUSIONS:In agreement with findings from our earlier published study, our findings support the observation that CL-K1 and their functional variants may be host factors associated with protection in schistosomiasis and may be a useful marker for further investigations.